Enhancement of Power Quality by mitigating of sag and swell problem in power system using DVR. Issue 1 (2022) - Kumar, Chandan; Ghosh, Pradipta; Chatterjee, Saibal
Abstract: In the present-day electric power system scenario, the custom of non-linear loads in power systems has ignited the investigation of power quality (PQ) problems in distribution systems like sag and swell. An effective control scheme is projected to enhance the voltage quality of subtle loads via a dynamic voltage restorer (DVR). Active Power Filter is one of the essential filters for mitigating power quality problems, and the controller is one of its integral parts. The simulation has been done using MATLAB/Simulink. The efficiency of the controller is illustrated by the results of the simulation.